CholedochoClip: A Case of Obstructive Jaundice 14 Years after Cholecystectomy - Grace E. Kim; John D. Morris; Peter E. Darwin (Case Reports in Gastrointestinal Medicine)
Gallstone disease is a common gastrointestinal pathology that may result in surgical intervention. While cholecystectomy has relatively minimal risks, surgical clip migration is a rare complication that can cause severe morbidity and mortality. This report describes a rare phenomenon of a biliary stone forming onto a migrated surgical clip 14 years after cholecystectomy causing an obstructive jaundice. This case illustrates the importance of keeping a migrated surgical clip on the differential when encountering patients with symptoms of cholangitis after cholecystectomy.